Between war and the state : civil society in South Vietnam, 1954-1975 - Nguyen-Marshall, Van, 1967- (Southeast Asia Program Publications, an imprint of Cornell University Press, 2023)
"Examines an array of voluntary activities, including mutual-help, professional, charitable, community development, student, women's, and rights organizations to explore state-society relations in wartime and provide insight into how ordinary South Vietnamese responded to a myriad of sociopolitical challenges that accompanied postcolonial nation building, national division, civil war, and Cold-War exigencies"-